Too much history per capita. The politics of war memory - Vukovar case study - Kardov, Kruno (2003)
This paper is based on an ethnographic research conducted during the year 2001. and 2002. in the city of Vukovar. Several things make Vukovar an interesting example. First, it is the Croatian city most destroyed in the war and also the city that suffered the greatest number of casualties. Second, its pre-war ethnic structure was relatively heterogeneous. And third, this area was peacefully reintegrated into the Republic of Croatia. The problem of war memory will be discussed through two layers: national and local, and two conflicting perspectives: Serbian and Croatian. On the national level - because of the great number of civilian causalties and three-months resistance under the siege the city of Vukovar has become significant simbol of human sacrifice in Croatian national narrative. By gaining the highly important place in the national symbolic repertoar, the characteristics of Vukovarian locality have been reduced. Local memories are articulated through different victim organisations, comemoration events, etc. and represented in everyday urban life by war monuments and street names. The relationship between the Croatian and Serbian war memories is more antagonistic and dissonant than dialectical and productive one. This can be seen on numerous examples - from emphasising different time periods to different understanding of certain war events and their meanings. The existance of separated Croatian and Serbian memorial graveyards is the best expression of this incompatibility.